Religion, emotion, sensation: affect theories and theologies - Bray, Karen; Moore, Stephen D. (Transdisciplinary theological colloquia, 2020)
"Religion, Emotion, Sensation asks what affect theory has to say about God or gods, religion or religions, scriptures, theologies, and liturgies. Contributors explore the crossings and criscrossings between affect theory and theology and the study of religion more broadly, as well as the political and social import of such work"--